Exploring Good Islamic Design Attributes Through the Lens of Asma-Ul-Husna: Towards a Universally Understood Good Design Evaluation Framework - Khairul Aidil Azlin Abd. Rahman; Nor Ziratul Aqma Norzaman; Nazlina Shaari; Nangkula Utaberta; Nayeem Asif; Wahyuni Zahrah (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2024)
This paper addresses the challenge of defining and evaluating good design, considering the different ways of thinking about what constitutes good Islamic Design in different populations and market segments. The lack of a standard definition raises important issues, such as limiting evaluation tools without a shared understanding. To address this issue, this paper examines the characteristics of good design and the evaluation criteria used by design competition platforms worldwide. The research is based on a qualitative methodology; keyword coding and linking analysis the evaluation criteria of seven prominent design competition platforms. By creating a common understanding of these attributes inspired by the divine attributes of Asma-ul-Husna, this paper will improve communication between designers and critics, allowing them to explore innovative design ideas more freely and confidently. It is intended for perceptions of good design to evolve and be influenced by changing aesthetics, as well as user needs brought about by technological advances. This study reveals a cyclical pattern in which design preferences emerge periodically, as seen in movements such as postmodernism. Therefore, the attributes of good design must be timeless and universal to ensure lasting relevance. This paper proposes an evaluation criterion that considers existing global standards and identifies seven timeless themes universally applicable to evaluating good design. This result highlights the need for further research, including expert opinion, to refine the proposed criteria. Creating a common basis for interpreting the hallmarks of good design from the perspective of the divine attributes of The Creator benefits designers and critics. It contributes to the enduring importance of good design in an evolving design environment.